2021
DOI: 10.3390/ma14092098
|View full text |Cite
|
Sign up to set email alerts
|

Crumpled Graphene-Storage Media for Hydrogen and Metal Nanoclusters

Abstract: Understanding the structural behavior of graphene flake, which is the structural unit of bulk crumpled graphene, is of high importance, especially when it is in contact with the other types of atoms. In the present work, crumpled graphene is considered as storage media for two types of nanoclusters—nickel and hydrogen. Crumpled graphene consists of crumpled graphene flakes bonded by weak van der Waals forces and can be considered an excellent container for different atoms. Molecular dynamics simulation is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The starting configuration, which is not yet a composite, but just the precursor—a system of graphene flakes with Ni nanoparticles inside each flake—is shown in Figure 1 , stage A . Note that in previous studies [ 39 , 40 , 41 ] it was shown that to obtain a Ni/graphene composite with high strength, it is necessary to take into account the difference in the diameter of Ni nanoparticle and the diameter of the rolled graphene flake. If the diameter of the nickel nanoparticle is large, then the graphene flake completely covers the nanoparticle, which makes the formation of strong bonds between the graphene flakes difficult, and therefore, complicates the composite fabrication.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The starting configuration, which is not yet a composite, but just the precursor—a system of graphene flakes with Ni nanoparticles inside each flake—is shown in Figure 1 , stage A . Note that in previous studies [ 39 , 40 , 41 ] it was shown that to obtain a Ni/graphene composite with high strength, it is necessary to take into account the difference in the diameter of Ni nanoparticle and the diameter of the rolled graphene flake. If the diameter of the nickel nanoparticle is large, then the graphene flake completely covers the nanoparticle, which makes the formation of strong bonds between the graphene flakes difficult, and therefore, complicates the composite fabrication.…”
Section: Methodsmentioning
confidence: 99%
“…The dimensions along x , y , and z directions are 100 Å, 101 Å, and 85 Å, respectively. A more detailed description of the formation of the starting configuration of the Ni/graphene composite is presented in [ 40 , 41 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The size of nickel nanoparticles was chosen because a rigid graphene flake interacting with given size nanoclusters destroys their crystal structure, which does not happen with larger nanoparticles. The dynamics of the interaction of a graphene flake with nickel nanoclusters of different sizes was described in detail in our early work [ 52 ]. Taking into account the peculiarity of the interaction of crumpled graphene with nickel nanoparticles, it is possible to achieve a denser structure of the metal/graphene composite with a smaller pore volume fraction.…”
Section: Methodsmentioning
confidence: 99%